A 47‐year‐old woman with hypercapnia and altered mental status. (20th June 2016) - Bellucci, Brian; Qiao, Renli
Abstract: Permissive hypercapnia is a commonly used ventilator strategy in attempt to improve refractory hypoxemia. The rationale of such practice is based on the assumption that hypercapnia, although associated with altered mental status, is well tolerated. Here, we report a case in which the altered mental status caused by hypercapnia is underlined by a life‐threatening mechanism. The case indicates the severity of hypercapnia may have been mistakenly overlooked in the past.